PiggyBac Transposon-Mediated CD19 Chimeric Antigen Receptor-T Cells Derived From CD45RA-Positive Peripheral Blood Mononuclear Cells Possess Potent and Sustained Antileukemic Function - Suematsu, Masaya; Yagyu, Shigeki; Nagao, Nobuyoshi; Kubota, Susumu; Shimizu, Yuto; Tanaka, Miyuki; Nakazawa, Yozo; Imamura, Toshihiko (Frontiers in Immunology, 2022)
The quality of chimeric antigen receptor (CAR)-T cell products, including memory and exhaustion markers, affects the long-term functionality of CAR-T cells. We previously reported that piggyBac (PB) transposon-mediated CD19 CAR-T cells exhibit a memory-rich phenotype that is characterized by the high proportion of CD45RA+/C-C chemokine receptor type 7 (CCR7)+ T-cell fraction. To further investigate the favorable phenotype of PB-CD19 CAR-T cells, we generated PB-CD19 CAR-T cells from CD45RA+ and CD45RA− peripheral blood mononuclear cells (PBMCs) (RA+ CAR and RA− CAR, respectively), and compared their phenotypes and antitumor activity. RA+ CAR-T cells showed better transient gene transfer efficiency 24 h after transduction and superior expansion capacity after 14 days of culture than those shown by RA− CAR-T cells. RA+ CAR-T cells exhibited dominant CD8 expression, decreased expression of the exhaustion marker programmed cell death protein-1 (PD-1) and T-cell senescence marker CD57, and enriched naïve/stem cell memory fraction, which are associated with the longevity of CAR-T cells. Transcriptome analysis showed that canonical exhaustion markers were downregulated in RA+ CAR-T, even after antigen stimulation. Although antigen stimulation could increase CAR expression, leading to tonic CAR signaling and exhaustion, the expression of CAR molecules on cell surface after antigen stimulation in RA+ CAR-T cells was controlled at a relatively lower level than that in RA− CAR-T cells. In the in-vivo stress test, RA+ CAR-T cells achieved prolonged tumor control with expansion of CAR-T cells compared with RA− CAR-T cells. CAR-T cells were not detected in the control or RA− CAR-T cells but RA+ CAR-T cells were expanded even after 50 days of treatment, as confirmed by sequential bone marrow aspiration. Our results suggest that PB-mediated RA+ CAR-T cells exhibit a memory-rich phenotype and superior antitumor function, thus CD45RA+ PBMCs might be considered an efficient starting material for PB-CAR-T cell manufacturing. This novel approach will be beneficial for effective treatment of B-cell malignancies.